Zapisać się dobrze w pamięci — listy Anny Mostowskiej do Józefa Zawadzkiego - Urbańska, Monika (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2011)
Anna Mostowska‘s literary works was unjustly depreciated. In Mostowska`s texts, we can find all genuine problems of the Enlightment, philosophical and existential considerations. Mostowska‘s ambition was to be membered. That`s why she improved her style, published with the most prominent editor, Joseph Zawadzki, and demanded careful proofreading from the publisher. She was an advocate of women‘s rights. She fought for women‘s status in social and literary (equal to men‘s). She earned her living by writing although her work wasn‘t popular with the nobility. Letters to Zawadzki testify her uncommon personality. We will discuss this problem in the study.